Meta Analysis of Ossa Pedis Radiographic Examination Procedures with Clinicalfracture - Martha Cory Adryanta Pandiangan; Marido Bisra; Devi Purnamasari; Shelly Angella (Journal of Mandalika Social Science, 2026)
The ossa pedis or foot bones are part of the lower extremities that are often affected by fractures, especially in the tarsal bones. Radiographic examination of ossa pedis fractures can be performed using several projections such as anteroposterior (AP), AP with a 10° cephalad angle, and oblique projections. This study aimed to determine the radiographic examination procedure of the ossa pedis in cases of tarsal fractures. The research used a meta-analysis method with a narrative and systematic review approach by analyzing relevant literature collected in May–June 2024. The analysis included patient preparation, equipment preparation, and examination procedures. The results showed that the anteroposterior (AP) projection is the most appropriate for examining ossa pedis with tarsal fractures because it follows standard operating procedures, produces clear diagnostic images, and is more efficient. In conclusion, the AP projection is an effective and efficient procedure to support accurate diagnosis of tarsal fractures.